Evolution of Corporate Criminal Liability Models and Theories under Indonesian New Criminal Code - Muhammad Wahyu Alfakar; Ali Masyhar; Cahya Wulandari; Ngboawaji Daniel Nte (Universitas Negeri Semarang, 2023)
Corporate crime, also known as white-collar crime, has persisted in Indonesia for decades, evolving alongside the country's economic and industrial growth. Various models and theories have emerged to address these issues, reflecting a growing recognition of the need for robust legal frameworks to combat corporate misconduct. Normative legal research methods have been employed in this study, focusing specifically on the criminal law aspects related to the development of corporate criminal liability theories and concepts under Law Number 1 of 2023. Law Number 1 of 2023 introduces the corporation as a maker and also a responsible corporation model of corporate criminal liability, recognizing corporations as legal entities capable of being held accountable for their actions. This statutory framework represents a significant advancement, reinforcing Supreme Court Regulation Number 13 of 2016. The research explores various perspectives on corporate responsibility models and theories, offering ideal solutions for their application and development within Indonesia's legal framework. This evolution signifies Indonesia's commitment to enhancing corporate accountability and ethical standards, aligning its legal principles with international norms while addressing domestic challenges. By integrating these models and theories into its legal system, Indonesia aims to foster a corporate culture that prioritizes compliance and ethical conduct, thereby mitigating the impact of corporate crime on society and promoting sustainable economic development.